Flow past a heated slippery corner - D’Alessio, Serge (Journal of physics. Conference series, 2024)
Discussed in this paper is the unsteady, laminar, two-dimensional, viscous flow around a corner subject to Navier-slip conditions characterized by a slip length, γ , with 0 ≤ γ ≤ 1. Comparisons with no-slip ( γ = 0) boundary conditions are made to assess the impact of a slippery surface. Both isothermal and heated flows are considered including forced and mixed convection. A numerical solution procedure utilizing boundary-layer coordinates is outlined. Numerous simulations have been compiled for the Reynolds number Re = 100 and Rayleigh numbers Ra = 0, 1, 10. Various results and comparisons are presented and discussed.